Lithium cobalt oxide positive electrode material, preparation method thereof and positive electrode sheet
Patent Information
- Application Number
- CN202510834886.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-06-20
AI Technical Summary
Lithium cobalt oxide cathode materials are prone to crystal structure phase transitions and Co dissolution under high voltage, which leads to rapid degradation of battery cycle performance. Moreover, existing technologies struggle to maintain stability while improving discharge specific capacity.
Multifunctional coatings are used, including low-temperature, medium-temperature and high-temperature coatings, to form electrochemical coatings, stabilizing coatings and fast-ion conductor coatings. Through multi-stage sintering, multiple fast channels for lithium ions are formed, and the lithium cobalt oxide crystal structure is stabilized.
It significantly improves the cycle performance and first-cycle efficiency of lithium cobalt oxide cathode materials, while maintaining the structural stability and capacity utilization of the materials under high voltage.
Smart Images

Figure CN120657099B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium cobalt oxide cathode material technology, and more specifically, to lithium cobalt oxide cathode materials, their preparation methods, and cathode sheets. Background Technology
[0002] Since its commercialization in the 1990s, lithium cobalt oxide (LCO) has been the most widely used cathode material in consumer lithium-ion batteries. The application voltage of LCO has gradually increased from the initial 4.2V to the current 4.50V, and the discharge specific capacity has also increased from 140mAh / g to 185mAh / g. However, the theoretical capacity of LCO is 274mAh / g, indicating that there is still significant room for improvement and development potential. Further increasing the discharge specific capacity of LCO requires raising the voltage to above 4.50V (e.g., at 4.6V, the discharge capacity is 220mAh / g). However, when the voltage exceeds 4.50V, the crystal structure of LCO undergoes a severe phase transition. At this point, the CoO6 octahedron is distorted due to the Jan Taylor effect, and the c-axis experiences severe collapse. At 4.55V, the lithium cobalt oxide crystal structure transforms from the O3 phase to the H1-3 phase, and at 4.60V, it further transforms to the O1 phase. This irreversible phase transition causes severe degradation of the crystal structure, leading to a rapid decline in the cycle performance of lithium cobalt oxide batteries. Simultaneously, because the lithium cobalt oxide cathode material uses micron-sized particles, at high voltages (>4.50V), the surface layer of these particles is the first to undergo delithiation, making it most susceptible to irreversible phase transitions. This results in the dissolution of Co in the cathode material, the release of active oxygen, and side reactions with the electrolyte, further deteriorating the cycle performance of the lithium cobalt oxide battery.
[0003] In view of this, the present invention is proposed. Summary of the Invention
[0004] The purpose of this invention is to provide a lithium cobalt oxide cathode material, its preparation method, and the cathode sheet thereof. Embodiments of this invention provide a novel lithium cobalt oxide cathode material that can significantly improve the cycle performance of batteries, while also increasing the first-cycle efficiency and discharge capacity.
[0005] This invention is implemented as follows:
[0006] In a first aspect, the present invention provides a lithium cobalt oxide cathode material, comprising a lithium cobalt oxide matrix and a multifunctional coating layer covering the lithium cobalt oxide matrix;
[0007] The lithium cobalt oxide matrix is LiCo. 1-x M xO2; wherein the doping element M includes any one or more of the following elements: Zn, Ti, Fe, Mg, Al, Y, La, Zr, Sr, W, Nb, Ta, Ba, Sb, Te, Bi, and Sn; 0.0001≤X≤0.1;
[0008] The multifunctional coating layer includes LiQO2, a compound that stabilizes lithium cobalt oxide crystals, and a fast ion conductor; wherein, Q in LiQO2 includes any one or more of Ni, Co, and Mn.
[0009] In an optional implementation, the Q element is derived from a low-temperature coating material with a melting point of 100-300°C;
[0010] Preferably, the compound is derived from a medium-temperature coating material with a melting point of 400-800°C; and the medium-temperature coating material includes oxides and metal halides;
[0011] Preferably, the fast ion conductor is derived from a high-temperature coating material with a melting point of 850-1000℃;
[0012] Preferably, the multifunctional coating layer includes an electrochemical coating layer with electrochemical properties formed by the low-temperature coating material, a stable coating layer that can stabilize lithium cobalt oxide crystals formed by the medium-temperature coating material, and a fast ion conductor coating layer formed by the high-temperature coating material.
[0013] Preferably, the multifunctional coating layer further includes multiple fast channels for lithium ions formed by fast ion conductors;
[0014] Preferably, the multifunctional coating layer further includes a polyanionic compound.
[0015] In an optional embodiment, the intermediate-temperature coating material includes any one or more of Sb2O3, Sb2O5, TeO2, Bi2O3, B2O3, MoO3, V2O5, SeO2, ZrCl4, and NaAlF4;
[0016] Preferably, the high-temperature coating material includes any one or more of Li3PO4, Li2SO4, LiF, LiBO2, and Li2B4O7;
[0017] Preferably, the low-temperature coating material includes nickel nitrate, cobalt nitrate, manganese nitrate, nickel formate, cobalt formate, manganese formate, and C. 10 H 16 CoO4, C 10 H 14 NiO4 and C 15 H 21 Any one or more of MnO6.
[0018] In an optional embodiment, the lithium cobalt oxide cathode material includes large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material, wherein the particle size of the large-particle lithium cobalt oxide cathode material is 16μm≤D. v50 The particle size of the small-particle lithium cobalt oxide cathode material is ≤20μm, and the particle size is 3μm≤D. v50 ≤6μm;
[0019] Preferably, the mass ratio of the large-particle lithium cobalt oxide cathode material to the small-particle lithium cobalt oxide cathode material is 2:1 to 4:1.
[0020] Secondly, the present invention provides a method for preparing the lithium cobalt oxide cathode material according to any one of the foregoing embodiments, comprising: mixing a lithium cobalt oxide matrix, a low-temperature coating material, a medium-temperature coating material, and a high-temperature coating material, and then performing multi-stage sintering.
[0021] Multi-stage sintering includes: low-temperature sintering, medium-temperature sintering, and high-temperature sintering.
[0022] In an optional embodiment, the lithium cobalt oxide matrix includes a large particle matrix and a small particle matrix;
[0023] Wherein, the particle size of the large particle matrix is 16μm≤D v50 ≤20μm; the particle size of the small particle matrix is 3μm≤D v50 ≤6μm;
[0024] Preferably, the mass ratio of the large particle matrix to the small particle matrix is 2:1 to 4:1.
[0025] In an optional embodiment, the preparation steps of the lithium cobalt oxide matrix include: mixing a cobalt source, a lithium source, and a dopant, followed by high-temperature sintering;
[0026] Preferably, the high-temperature sintering conditions for forming the large particle matrix include: a temperature of 1020-1060°C and a time of 8-12 hours;
[0027] The high-temperature sintering conditions for forming the small particle matrix include: a temperature of 980-1030℃ and a time of 8-12 hours;
[0028] Preferably, the cobalt source includes a large-particle cobalt source and a small-particle cobalt source;
[0029] The large-particle cobalt source has a particle size of 14 μm ≤ D. v50 ≤18μm; the particle size of the small cobalt source is 2μm≤D v50 ≤7μm;
[0030] Preferably, the molar ratio of Co in the cobalt source to Li in the lithium source is Li / Co = 1.02 to 1.09:1;
[0031] Preferably, the amount of the dopant is calculated based on the content of the corresponding dopant element in the lithium cobalt oxide matrix, and the mass percentage of the dopant element in the lithium cobalt oxide matrix is 300-1000 ppm.
[0032] Preferably, the doping element in the dopant includes any one or more of Zn, Ti, Fe, Mg, Al, Y, La, Zr, Sr, W, Nb, Ta, Ba, Sb, Te, Bi, and Sn;
[0033] Preferably, the cobalt source includes any one or more of cobalt carbonate, cobalt tetroxide, cobalt hydroxyoxide, cobalt hydroxide, and cobalt oxalate;
[0034] Preferably, the lithium source includes any one or more of lithium carbonate, lithium hydroxide, and lithium oxide.
[0035] In optional embodiments, the conditions for low-temperature sintering in multi-stage sintering include: a temperature of 100-300℃ and a holding time of 3-5 hours; and / or,
[0036] The conditions for medium-temperature sintering include: 400-800℃, with a holding time of 3-5 hours; and / or,
[0037] The conditions for high-temperature sintering include: 850-1000℃, and a holding time of 3-5 hours.
[0038] In an optional embodiment, the low-temperature coating material contains any one or more of the following elements: Ni, Co, and Mn; and the mass of each element accounts for 300-1000 ppm of the lithium cobalt oxide matrix.
[0039] The intermediate-temperature coating material contains any one or more of the following elements: Sb, Te, Bi, B, Mo, V, Se, Zr, Al, and Na; and the mass of each element accounts for 300-1000 ppm of the lithium cobalt oxide matrix.
[0040] Each of the high-temperature coating materials accounts for 1000-2000 ppm of the lithium cobalt oxide matrix.
[0041] Thirdly, the present invention provides a positive electrode sheet comprising the lithium cobalt oxide positive electrode material described in any of the foregoing embodiments.
[0042] The present invention has the following beneficial effects: by selecting different coating materials, a multifunctional coating layer with multiple functions can be formed on the surface of lithium cobalt oxide substrate, which can improve the stability of lithium cobalt oxide cathode material during charge and discharge process and improve cycle performance. Attached Figure Description
[0043] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0044] Figure 1 This invention provides a schematic diagram of a process for preparing lithium cobalt oxide cathode materials.
[0045] Figure 2 This is a SEM image of the lithium cobalt oxide cathode material provided in Example 4 of the present invention;
[0046] Figure 3 This is a SEM image of the lithium cobalt oxide cathode material provided in Comparative Example 13 of the present invention;
[0047] Figure 4 The image shows the XRD pattern of the lithium cobalt oxide cathode material provided in Example 3 of this invention. Detailed Implementation
[0048] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0049] In a first aspect, embodiments of the present invention provide a lithium cobalt oxide cathode material, comprising a lithium cobalt oxide matrix, which is LiCo... 1- x M x O2; wherein the dopant element M includes any one or more of the following elements: Zn, Ti, Fe, Mg, Al, Y, La, Zr, Sr, W, Nb, Ta, Ba, Sb, Te, Bi, and Sn. 0.0001≤X≤0.1; for example, 0.0001, 0.005, 0.01, 0.05, 0.1, or any other value between 0.0001 and 0.1.
[0050] It also includes a multifunctional coating layer covering the lithium cobalt oxide substrate; the multifunctional coating layer includes LiQO2, a compound stabilizing lithium cobalt oxide crystals, and a fast ion conductor; wherein, Q in LiQO2 includes any one or more of Ni, Co, and Mn, and the Q element is derived from a low-temperature coating material with a melting point of 100-300℃; the compound stabilizing lithium cobalt oxide crystals is derived from a medium-temperature coating material with a melting point of 400-800℃, and the medium-temperature coating material includes oxides and metal halides; the fast ion conductor is derived from a high-temperature coating material with a melting point of 850-1000℃.
[0051] The low-temperature coating material of this invention preferentially reacts with residual lithium on the surface of the lithium cobalt oxide substrate to form one or more of LiCoO2, LiNiO2, and LiMnO2, generating a coating layer with certain electrochemical properties on the surface of the lithium cobalt oxide substrate, while further reducing the residual lithium on the surface of the lithium cobalt oxide substrate. The medium-temperature coating material can stably coat the surface of the lithium cobalt oxide substrate. Simultaneously, specific elements contained in the medium-temperature coating material can be doped into the shallow surface region of the lithium cobalt oxide substrate, stabilizing the crystal structure of the lithium cobalt oxide substrate surface. The high-temperature coating material can coat the surface of the lithium cobalt oxide substrate and form multiple fast channels for lithium ions, which is beneficial for lithium ion insertion / extraction and ensures normal capacity utilization. Furthermore, the above-mentioned coating materials can react with each other to generate polyanionic compounds. These polyanionic compounds have high voltage stability, and coating the surface of the lithium cobalt oxide substrate can maintain the stability of the lithium cobalt oxide battery during charge and discharge, improving its cycle performance.
[0052] As can be seen, the multifunctional coating layer provided in this embodiment of the invention is formed by the aforementioned low-temperature coating material, medium-temperature coating material, and high-temperature coating material. Specifically, the low-temperature coating material forms an electrochemical coating layer with certain electrochemical properties, the medium-temperature coating material forms a stable coating layer that can stabilize lithium cobalt oxide crystals, and the high-temperature coating material forms a fast-ion conductor coating layer. Simultaneously, the high-temperature coating material can form multiple fast channels for lithium ions within the multifunctional coating layer, which is beneficial for lithium ion insertion / extraction and ensures normal capacity utilization. Furthermore, the coating materials with different melting points can react with each other to form polyionic compounds. These polyanionic compounds have high voltage stability, and when coated on the surface of lithium cobalt oxide, they can maintain structural stability during charge and discharge processes, improving cycle performance.
[0053] It should be noted that (1) the electrochemical coating layer, the stable coating layer, and the fast ion conductor coating layer are not absolutely arranged in sequence, but may be arranged in a cross manner. For example, the stable coating layer or the fast ion conductor coating layer may be interspersed in the electrochemical coating layer. The coating layer does not completely cover the lithium cobalt oxide substrate, and there may be partial coating.
[0054] (2) The residual lithium on the surface of the lithium cobalt oxide matrix is the lithium that remains during the preparation of the lithium cobalt oxide matrix.
[0055] Furthermore, the aforementioned low-temperature coating material includes raw materials with a melting point of 100-300℃ capable of coating a lithium cobalt oxide matrix and reacting with residual lithium on its surface. Examples include, but are not limited to, nickel nitrate, cobalt nitrate, manganese nitrate, nickel formate, cobalt formate, manganese formate, and C. 10 H 16 CoO4, C 10 H 14 NiO4 and C 15 H 21 Any one or more of MnO6. In this embodiment of the invention, the above-mentioned substances are used to enable better reaction with residual lithium on the surface of the lithium cobalt oxide substrate, resulting in a coating layer with better electrochemical performance and further reducing residual lithium on the surface of the lithium cobalt oxide substrate.
[0056] Furthermore, the intermediate-temperature coating material with a melting point of 400-800℃ includes oxides and metal halides with a melting point of 400-800℃ capable of coating the lithium cobalt oxide matrix. For example, it includes, but is not limited to, any one or more of Sb₂O₃, Sb₂O₅, TeO₂, Bi₂O₃, B₂O₃, MoO₃, V₂O₅, SeO₂, ZrCl₄, and NaAlF₄. In preferred embodiments of the present invention, the above-mentioned materials not only stably coat the surface of the lithium cobalt oxide matrix, but also dope the shallow surface region of the lithium cobalt oxide matrix with elements such as Sb, Te, Bi, B, Mo, V, Se, Zr, and Na, stabilizing the crystal structure of the lithium cobalt oxide matrix surface.
[0057] Furthermore, the high-temperature coating material with a melting point of 850-1000℃ includes substances with a melting point of 850-1000℃ capable of coating a lithium cobalt oxide substrate, such as, but not limited to, any one or more of Li3PO4, Li2SO4, LiF, LiBO2, and Li2B4O7. The substances provided in this embodiment of the invention can not only coat the surface of the lithium cobalt oxide substrate, but also form various fast channels for lithium ions in the multifunctional coating layer, which is beneficial for lithium ion insertion / extraction and ensures normal capacity utilization. The coating materials provided in the embodiments of the present invention can react with each other to generate polyanionic compounds containing elements such as Ni, Co, Mn, Li, Sb, Te, Bi, B, Mo, V, and Se, such as LiCoSb(PO4)2, LiNiMo(PO4)3, LiMnSb(PO4)2, Li2CoTe(SO4)4, LiNiBi(SO4)3, LiMnB(SO4)3, and LiCoSb(B4O7)3. These polyanionic materials have high voltage stability, and when coated on the surface of lithium cobalt oxide, they can maintain the stability of the structure during the charge and discharge process, thereby improving cycle performance.
[0058] The lithium cobalt oxide cathode material provided in this embodiment of the invention includes large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material, wherein the particle size of the large-particle lithium cobalt oxide cathode material is 16μm≤Dv50≤20μm, and the particle size of the small-particle lithium cobalt oxide cathode material is 3μm≤Dv50≤6μm.
[0059] It should be noted that the lithium cobalt oxide cathode material can be made of only large-particle lithium cobalt oxide cathode material, only small-particle lithium cobalt oxide cathode material, or a combination of both.
[0060] When the combination is a large-particle lithium cobalt oxide cathode material and a small-particle lithium cobalt oxide cathode material, the mass ratio of the large-particle lithium cobalt oxide cathode material to the small-particle lithium cobalt oxide cathode material is 2:1-4:1.
[0061] Using two different particle sizes is beneficial for compacting lithium cobalt oxide cathode materials, which in turn helps to improve their capacity and energy density.
[0062] Secondly, embodiments of the present invention provide a method for preparing the above-mentioned lithium cobalt oxide cathode material, the process flow diagram of which is shown below. Figure 1 The specific preparation steps include:
[0063] S1. Preparation of lithium cobalt oxide matrix;
[0064] The cobalt source, lithium source and dopant are mixed and then sintered at high temperature.
[0065] Since the lithium cobalt oxide cathode material provided in this embodiment of the invention includes both large-particle and small-particle lithium cobalt oxide cathode materials, it is necessary to prepare large-particle and small-particle substrates of different particle sizes when preparing the lithium cobalt oxide matrix. Correspondingly, cobalt sources of different particle sizes will be used. That is, the cobalt source includes large-particle and small-particle cobalt sources; wherein, the particle size of the large-particle cobalt source is 14μm≤D. v50 ≤18μm; the particle size of the small cobalt source is 2μm≤D v50 ≤7μm; Using large and small cobalt sources of different particle sizes is beneficial for the subsequent formation of large and small lithium cobalt oxide cathode materials, respectively.
[0066] The maximum particle size of the small cobalt source is 7 micrometers. It is a polycrystalline particle formed by the accumulation of primary particles. During the sintering process, the primary particles will fuse and grow together, which will cause the polycrystalline particles to break down and form a small particle matrix. The maximum particle size of the small particle matrix is 6 micrometers.
[0067] Furthermore, the aforementioned small-particle cobalt source and large-particle cobalt source can be separately mixed with a lithium source and a dopant and sintered to form large-particle and small-particle matrices, respectively. Then, the two can be subjected to subsequent operations independently or mixed again for further operations. Alternatively, the large-particle cobalt source, small-particle cobalt source, lithium source, and dopant can be mixed and sintered to form a lithium cobalt oxide matrix with a mixture of large and small-particle matrices. This embodiment of the invention uses the example of separately mixing and sintering small-particle and large-particle cobalt sources with a lithium source and a dopant to form large and small-particle matrices, respectively, as an example. Preparing large and small-particle matrices separately is beneficial for controlling their particle size, thereby improving the performance of the lithium cobalt oxide cathode material.
[0068] Furthermore, in the embodiments of the present invention, the cobalt source can be selected from commercially available cobalt sources, such as, but not limited to, any one or more of cobalt carbonate, cobalt tetroxide, cobalt hydroxyoxide, cobalt hydroxide, and cobalt oxalate.
[0069] Furthermore, in the embodiments of the present invention, the lithium source can also be selected from commercially available lithium sources, such as, but not limited to, any one or more of lithium carbonate, lithium hydroxide, and lithium oxide.
[0070] In this embodiment of the invention, the molar ratio of Co in the cobalt source to Li in the lithium source is Li / Co = 1.02 to 1.09:1; for example, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, or any other value between 1.02 and 1.09:1. Using the above ratio is more conducive to the formation of a lithium cobalt oxide matrix and to improving the capacity of the lithium cobalt oxide cathode material.
[0071] Furthermore, in the embodiments of the present invention, the doping element in the dopant includes any one or more of Zn, Ti, Fe, Mg, Al, Y, La, Zr, Sr, W, Nb, Ta, Ba, Sb, Te, Bi, and Sn.
[0072] The amount of dopant used is calculated based on the content of the dopant element in the lithium cobalt oxide matrix. Specifically, the mass percentage of the dopant element in the lithium cobalt oxide matrix is 300-1000 ppm. If the proportion of the dopant element is too high, it may affect the capacity of the lithium cobalt oxide cathode material; if the proportion is too low, it may affect the cycle performance.
[0073] Furthermore, in this embodiment of the invention, the high-temperature sintering conditions for forming the large particle matrix include: a temperature of 1020-1060℃ and a time of 8-12 hours; the high-temperature sintering conditions for forming the small particle matrix include: a temperature of 980-1030℃ and a time of 8-12 hours. Using the above-described sintering methods is beneficial for forming both large and small particle matrices.
[0074] After sintering, the material needs to undergo post-processing such as jaw crusher, roller crusher, and pulverizer. The methods and steps of the above post-processing are all existing operations, and will not be described in detail in the embodiments of the present invention.
[0075] S2, forming lithium cobalt oxide cathode material;
[0076] The lithium cobalt oxide matrix, low-temperature coating material, medium-temperature coating material and high-temperature coating material are mixed and then sintered in multiple stages.
[0077] The lithium cobalt oxide cathode material includes both large-particle and small-particle lithium cobalt oxide cathode materials. In this case, the lithium cobalt oxide matrix consists of both large-particle and small-particle matrices, with a mass ratio of 2:1 to 4:1. For example, it can be any value between 2:1, 3:1, 4:1, or 2:1-4:1.
[0078] Furthermore, in this embodiment of the invention, the low-temperature coating material includes raw materials with a melting point of 100-300℃ capable of coating a lithium cobalt oxide matrix and reacting with residual lithium on its surface. Examples include, but are not limited to, nickel nitrate, cobalt nitrate, manganese nitrate, nickel formate, cobalt formate, manganese formate, and C. 10 H 16 CoO4, C 10 H 14 NiO4 and C 15 H 21 Any one or more of MnO6.
[0079] The low-temperature coating material contains any one or more of Ni, Co, and Mn: the mass percentage of each of the above elements is 300-1000 ppm of the lithium cobalt oxide matrix. For example, it is 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm or any value between 300-1000 ppm.
[0080] Furthermore, in the embodiments of the present invention, the medium-temperature coating material includes raw materials with a melting point of 400-800℃ that can coat a lithium cobalt oxide matrix. For example, it includes, but is not limited to, any one or more of Sb2O3, Sb2O5, TeO2, Bi2O3, B2O3, MoO3, V2O5, SeO2, ZrCl4, and NaAlF4.
[0081] The intermediate-temperature coating material contains any one or more of Sb, Te, Bi, B, Mo, V, Se, Zr, Al, and Na, with each of the above elements accounting for 300-1000 ppm of the lithium cobalt oxide matrix by mass. For example, it is 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, or any value between 300-1000 ppm.
[0082] Furthermore, in the embodiments of the present invention, the high-temperature coating material includes a material with a melting point of 850-1000℃ that can be coated on a lithium cobalt oxide matrix, such as, but not limited to, any one or more of Li3PO4, Li2SO4, LiF, LiBO2 and Li2B4O7.
[0083] Each of the aforementioned high-temperature coating materials accounts for 1000-2000 ppm of the lithium cobalt oxide matrix. For example, it is any value between 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, or 1000-2000 ppm.
[0084] Using the above-mentioned proportions of low-temperature coating materials, medium-temperature coating materials, and high-temperature coating materials enables these coating materials to fully react and form polyanionic compounds during high-temperature sintering, thereby further improving the stability and cycle performance of lithium cobalt oxide cathode materials.
[0085] Furthermore, the multi-stage sintering in this embodiment of the invention includes: low-temperature sintering, medium-temperature sintering, and high-temperature sintering. Specifically, after low-temperature sintering, medium-temperature sintering and high-temperature sintering are performed directly in sequence, with the temperature being raised directly after each sintering, without cooling and then raising the temperature again.
[0086] Specifically, the conditions for low-temperature sintering include: a temperature of 100-300℃ and a holding time of 3-5 hours. For example, the low-temperature sintering temperature can be any value between 100℃, 150℃, 200℃, 250℃, 300℃, or 100-300℃. The holding time can be any value between 3 hours, 4 hours, 5 hours, or 3-5 hours.
[0087] The conditions for medium-temperature sintering include: 400-800℃, with a holding time of 3-5 hours. For example, the medium-temperature sintering temperature can be any value between 400℃, 500℃, 600℃, 700℃, 800℃, or 400-800℃. The holding time can be any value between 3 hours, 4 hours, 5 hours, or 3-5 hours.
[0088] The conditions for high-temperature sintering include: 850-1000℃, with a holding time of 3-5 hours. For example, the high-temperature sintering temperature can be any value between 850℃, 900℃, 950℃, 1000℃, or 850-1000℃. The holding time can be any value between 3 hours, 4 hours, 5 hours, or 3-5 hours.
[0089] Using the above conditions for multi-stage sintering is beneficial for the formation of corresponding functional layers of low-temperature coating materials, medium-temperature coating materials and high-temperature coating materials, and is also beneficial for the formation of fast channels and polyanionic compounds, thereby ensuring the performance of lithium cobalt oxide cathode materials.
[0090] The heating rate during the multi-stage sintering process described above is 1-3℃ / min.
[0091] The material after multi-stage sintering also undergoes post-processing such as jaw crusher, roller crusher and pulverizer.
[0092] It should be noted that the embodiments of the present invention illustrate the formation of a lithium cobalt oxide cathode material comprising large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material by multi-stage sintering of a mixture of large-particle matrix, small-particle matrix, low-temperature coating material, high-temperature coating material, and medium-temperature coating material. However, it is understood that large-particle matrix and small-particle matrix can also be separately mixed with low-temperature coating material, high-temperature coating material, and medium-temperature coating material for multi-stage sintering to form large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material respectively, and then the two can be mixed in proportion to form the desired lithium cobalt oxide cathode material. Alternatively, the lithium cobalt oxide cathode material may consist only of large-particle lithium cobalt oxide cathode material or small-particle lithium cobalt oxide cathode material. The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0093] Example 1
[0094] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0095] (1) D v50Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (16μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.06:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the large-particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace, heated to 1050℃ at a heating rate of 3℃ / min, and sintered at this temperature for 10 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 19.0 μm.
[0096] (2) D v50 A 19.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0097] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0098] Comparative Examples 1-3
[0099] Comparative Examples 1-3 provide methods for preparing lithium cobalt oxide cathode materials, which are basically the same as those provided in Example 1, except that the operations in steps (2) and (3) are different. The remaining operations are the same as those in Example 1, as follows:
[0100] Comparative Example 1
[0101] The coating material used in step (2) is only low-temperature coating material manganese formate (Mn element mass ratio of 500ppm of large particle matrix), and medium-temperature coating materials and high-temperature coating materials are not used.
[0102] Step (3) involves only low-temperature sintering at 300℃ for 4 hours. Medium-temperature sintering and high-temperature sintering are not performed.
[0103] Comparative Example 2
[0104] The coating material used in step (2) is only Bi2O3 (Bi mass ratio of 500ppm of large particle matrix) at medium temperature, and no low temperature coating material or high temperature coating material is used.
[0105] Step (3) involves only sintering at a medium temperature of 800℃ for 4 hours, without performing low-temperature sintering or high-temperature sintering.
[0106] Comparative Example 3
[0107] In step (2), the coating material is the high-temperature coating material Li2B4O7 (the mass percentage of Li2B4O7 is 1000ppm of the large particle matrix), and low-temperature coating materials and medium-temperature coating materials are not used.
[0108] Step (3) involves only high-temperature sintering at 950°C for 4 hours, without low-temperature sintering or medium-temperature sintering.
[0109] Example 2
[0110] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0111] (1) D v50 The chemical substances, consisting of 3.5μm small particles of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide, were weighed according to a lithium / cobalt source ratio of Li / Co = 1.03:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the small particle matrix. The weighed materials were then premixed in a self-sealing bag and added to a Kawada mixer, first at 200 rpm for 5 min, then at 1200 rpm for 20 min. The uniformly mixed material was then placed in a mortar and placed in a box furnace, heated to 1030℃ at a heating rate of 3℃ / min, and sintered at this temperature for 10 h. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a small particle matrix of 5.0 μm.
[0112] (2) D v50A 5.0 μm small particle matrix, a low-temperature coating material nickel formate (Ni element mass ratio of 500 ppm of the small particle matrix), a medium-temperature coating material TeO2 (Te mass ratio of 500 ppm of the small particle matrix), and a high-temperature coating material LiF (LiF mass ratio of 1000 ppm of the small particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2. The mixture was stirred at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0113] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 750℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain small particles of lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0114] Comparative Examples 4-6
[0115] Comparative Examples 4-6 provide methods for preparing lithium cobalt oxide cathode materials, which are basically the same as those provided in Example 2, except that the operations in steps (2) and (3) are different. The remaining operations are the same as those in Example 2, as follows:
[0116] Comparative Example 4
[0117] The coating material used in step (2) is only the low-temperature coating material nickel formate (Ni element mass ratio is 500ppm of small particle matrix), and medium-temperature coating materials and high-temperature coating materials are not used.
[0118] Step (3) involves only low-temperature sintering at 300℃ for 4 hours. Medium-temperature sintering and high-temperature sintering are not performed.
[0119] Comparative Example 5
[0120] The coating material used in step (2) is only the medium-temperature coating material TeO2 (Te mass ratio is 500ppm of the small particle matrix), and low-temperature coating materials and high-temperature coating materials are not used.
[0121] Step (3) involves only sintering at a constant temperature of 750°C for 4 hours, without performing low-temperature sintering or high-temperature sintering.
[0122] Comparative Example 6
[0123] The coating material used in step (2) is only the high-temperature coating material LiF (LiF mass ratio is 1000ppm of the small particle matrix), and low-temperature coating materials and medium-temperature coating materials are not used.
[0124] Step (3) involves only high-temperature sintering at 900℃ for 4 hours, without low-temperature sintering or medium-temperature sintering.
[0125] Example 3
[0126] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0127] (1) Refer to Examples 1 and 2.
[0128] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. A low-temperature coating material, cobalt nitrate (Co element mass percentage of 500 ppm in the lithium cobalt oxide matrix), a medium-temperature coating material, Sb₂O₃ (Sb mass percentage of 500 ppm in the lithium cobalt oxide matrix), and a high-temperature coating material, Li₃PO₄ (Li₃PO₄ mass percentage of 1000 ppm in the lithium cobalt oxide matrix), are mixed. The mixed materials are then processed using a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1 at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0129] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 700℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0130] Comparative Examples 7-9
[0131] Comparative Examples 7-9 each provide a method for preparing lithium cobalt oxide cathode material. This method is basically the same as the method provided in Example 3, except that the operations in steps (2) and (3) are different. The remaining operations are the same as in Example 3, as follows:
[0132] Comparative Example 7
[0133] The coating material used in step (2) is only low-temperature coating material cobalt nitrate (Co element mass ratio is 500ppm of lithium cobalt oxide matrix), and medium-temperature coating materials and high-temperature coating materials are not used.
[0134] Step (3) involves only low-temperature sintering at 300℃ for 4 hours. Medium-temperature sintering and high-temperature sintering are not performed.
[0135] Comparative Example 8
[0136] The coating material used in step (2) is only Sb2O3 (Sb mass percentage is 500ppm of lithium cobalt oxide matrix) at medium temperature, and no low temperature coating material or high temperature coating material is used.
[0137] Step (3) involves only sintering at a constant temperature of 700℃ for 4 hours, without performing low-temperature sintering or high-temperature sintering.
[0138] Comparative Example 9
[0139] In step (2), the coating material is the high-temperature coating material Li3PO4 (Li3PO4 mass percentage is 1000ppm of the lithium cobalt oxide matrix), and low-temperature coating materials and medium-temperature coating materials are not used.
[0140] Step (3) involves only high-temperature sintering at 900℃ for 4 hours, without low-temperature sintering or medium-temperature sintering.
[0141] Examples 4-5
[0142] Examples 4-5 provide a method for preparing lithium cobalt oxide cathode material, which is basically the same as the method provided in Example 3, except that the operations in steps (2) and (3) are different. The remaining operations are the same as in Example 3, as follows:
[0143] Example 4
[0144] In step (2), the low-temperature coating material is cobalt acetylacetone and nickel nitrate; the medium-temperature coating material is Sb2O3 and TeO2 (where Co, Ni, Sb and Te account for 500 ppm of the lithium cobalt oxide matrix respectively); and the high-temperature coating material is Li3PO4 and LiF (Li3PO4 and LiF account for 1000 ppm of the lithium cobalt oxide matrix respectively).
[0145] In step (3), the sintering process consists of three temperature gradients. First, the temperature is at a low temperature plateau of 300℃, and sintered at a constant temperature for 4 hours. Then, the temperature is increased to a medium temperature plateau of 750℃ at a heating rate of 2℃ / min, and sintered at a constant temperature for 4 hours. Finally, the temperature is increased to a high temperature plateau of 850℃ at a heating rate of 2℃ / min, and sintered at a constant temperature for 4 hours.
[0146] Example 5
[0147] In step (2), the low-temperature coating materials are cobalt acetylacetonate, nickel nitrate and manganese formate; the medium-temperature coating materials are Sb2O3, TeO2, Bi2O3 (the mass percentages of Co, Ni, Mn, Sb, Te and Bi are 500 ppm of the lithium cobalt oxide matrix); and the high-temperature coating materials are Li3PO4, LiF, Li2B4O7 (the mass percentages of Li3PO4, LiF and Li2B4O7 are 1000 ppm of the lithium cobalt oxide matrix).
[0148] In step (3), the sintering process consists of three temperature gradients. First, the temperature is at a low-temperature plateau of 300℃, and sintered at a constant temperature for 4 hours. Then, the temperature is increased to a medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at a constant temperature for 4 hours. Finally, the temperature is increased to a high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at a constant temperature for 4 hours.
[0149] Comparative Example 10
[0150] This comparative example provides a lithium cobalt oxide cathode material, which is the D from Example 1. v50 It is a large particle matrix of 19.0 μm.
[0151] Comparative Example 11
[0152] This comparative example provides a lithium cobalt oxide cathode material, which is the D from Example 2. v50 It is a small particle matrix of 5.0 μm.
[0153] Comparative Example 12
[0154] This comparative example provides a method for preparing a lithium cobalt oxide cathode material, including:
[0155] (1) Refer to Examples 1 and 2.
[0156] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a size of 5.0 μm and a mass ratio of large particles to small particles of 4:1. The two are mixed together, and the mixed material is then processed using a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1.2. The mixture is stirred at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0157] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to 900℃ at a heating rate of 2℃ / min, and sintered at a constant temperature for 12 hours. Then it was allowed to cool naturally to room temperature. Sintering was carried out in an air atmosphere with an air flow rate of 3m³ / min. 3 / h, after cooling, the material is crushed by mechanical grinding to obtain D v50The lithium cobalt oxide particles are 16.1 μm in size.
[0158] Comparative Example 13
[0159] This comparative example provides a method for preparing a lithium cobalt oxide cathode material, including:
[0160] (1) Refer to Examples 1 and 2.
[0161] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles (5.0 μm) and a large particle to small particle matrix mass ratio of 4:1, forming a lithium cobalt oxide matrix. Low-temperature coatings include cobalt nitrate and nickel formate; medium-temperature coatings include Sb₂O₃ and TeO₂ (Co, Ni, Sb, and Te mass percentages are 500 ppm of the lithium cobalt oxide matrix); and high-temperature coatings include Li₃PO₄ and LiF (Li₃PO₄ and LiF mass percentages are 1000 ppm of the lithium cobalt oxide matrix). The mixed materials are then processed using a ball mill at 200 rpm for 3 hours to achieve uniform mixing, yielding a secondary mixture.
[0162] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 12 hours. Then, it was allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is crushed by mechanical grinding to obtain D v50 The lithium cobalt oxide particles are 16.1 μm in size.
[0163] Example 6
[0164] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0165] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (14μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.06:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the large-particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1060℃ at a rate of 3℃ / min, and sintered at this temperature for 12 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min.3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 19.0 μm.
[0166] (2) D v50 A 19.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0167] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0168] Example 7
[0169] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0170] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (18μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.06:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the large-particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1020℃ at a rate of 3℃ / min, and sintered at this constant temperature for 8 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 19.0 μm.
[0171] (2) D v50 A 19.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0172] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0173] Example 8
[0174] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0175] (1) D v50 The chemical substances, consisting of 2μm small particles of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide, were weighed according to a lithium / cobalt source ratio of Li / Co = 1.03:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the small particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace, heated to 1030℃ at a heating rate of 3℃ / min, and sintered at this temperature for 12 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a small particle matrix of 5.0 μm.
[0176] (2) D v50A 5.0 μm small particle matrix, a low-temperature coating material nickel formate (Ni element mass ratio of 500 ppm of the small particle matrix), a medium-temperature coating material TeO2 (Te mass ratio of 500 ppm of the small particle matrix), and a high-temperature coating material LiF (LiF mass ratio of 1000 ppm of the small particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2. The mixture was stirred at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0177] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 750℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain small particles of lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0178] Example 9
[0179] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0180] (1) D v50 The chemical substances, consisting of 7μm small particles of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide, were weighed according to a lithium / cobalt source ratio of Li / Co = 1.03:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the small particle matrix. The weighed materials were then premixed in a self-sealing bag and added to a Kawada mixer, first at 200 rpm for 5 minutes, then at 1200 rpm for 20 minutes. The uniformly mixed material was then placed in a mortar and placed in a box furnace, heated to 980℃ at a heating rate of 3℃ / min, and sintered at this temperature for 8 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a small particle matrix of 5.0 μm.
[0181] (2) D v50A 5.0 μm small particle matrix, a low-temperature coating material nickel formate (Ni element mass ratio of 500 ppm of the small particle matrix), a medium-temperature coating material TeO2 (Te mass ratio of 500 ppm of the small particle matrix), and a high-temperature coating material LiF (LiF mass ratio of 1000 ppm of the small particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2. The mixture was stirred at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0182] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 750℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain small particles of lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0183] Example 10
[0184] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0185] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (14μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.06:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the large-particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1030℃ at a rate of 3℃ / min, and sintered at this temperature for 8 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 16.0 μm.
[0186] (2) D v50A 16.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0187] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0188] Example 11
[0189] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0190] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (18μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.06:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the large-particle matrix. The weighed materials were premixed in self-sealing bags, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1040℃ at a rate of 3℃ / min, and sintered at this temperature for 10 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 20.0 μm.
[0191] (2) D v50A 20.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0192] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0193] Example 12
[0194] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0195] (1) D v50 The chemical substances, consisting of 2μm small particles of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide, were weighed according to a lithium / cobalt source ratio of Li / Co = 1.03:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the small particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace, heated to 980℃ at a heating rate of 3℃ / min, and sintered at this temperature for 8 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a small particle matrix of 3.0 μm.
[0196] (2) D v50A 3.0 μm small particle matrix, a low-temperature coating material nickel formate (Ni element mass ratio of 500 ppm of the small particle matrix), a medium-temperature coating material TeO2 (Te mass ratio of 500 ppm of the small particle matrix), and a high-temperature coating material LiF (LiF mass ratio of 1000 ppm of the small particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0197] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 750℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain small particles of lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0198] Example 13
[0199] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0200] (1) D v50 The chemical substances, consisting of 4μm small particles of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide, were weighed according to a lithium / cobalt source ratio of Li / Co = 1.03:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the small particle matrix. The weighed materials were then premixed in a self-sealing bag and added to a Kawada mixer, first at 200 rpm for 5 min, then at 1200 rpm for 20 min. The uniformly mixed material was then placed in a mortar and placed in a box furnace, heated to 1010℃ at a heating rate of 3℃ / min, and sintered at this temperature for 11 h. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a small particle matrix of 6.0 μm.
[0201] (2) D v50A 6.0 μm small particle matrix, a low-temperature coating material nickel formate (Ni element mass ratio of 500 ppm of the small particle matrix), a medium-temperature coating material TeO2 (Te mass ratio of 500 ppm of the small particle matrix), and a high-temperature coating material LiF (LiF mass ratio of 1000 ppm of the small particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1.2. The mixture was stirred at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0202] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 750℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain small particles of lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0203] Example 14
[0204] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0205] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (16μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.02:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the large-particle matrix. The weighed materials were premixed in self-sealing bags, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1060℃ at a rate of 3℃ / min, and sintered at this temperature for 12 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 19.0 μm.
[0206] (2) D v50A 19.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0207] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0208] Example 15
[0209] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0210] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (16μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.09:1 mol / mol, with each dopant element having a mass percentage of 500 ppm in the large-particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1030℃ at a rate of 3℃ / min, and sintered at this temperature for 10 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 19.0 μm.
[0211] (2) D v50A 19.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0212] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0213] Example 16
[0214] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0215] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (16μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.06:1 mol / mol, with each dopant element having a mass percentage of 300 ppm in the large-particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1060℃ at a rate of 3℃ / min, and sintered at this temperature for 12 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 19.0 μm.
[0216] (2) D v50A 19.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0217] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0218] Example 17
[0219] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0220] (1) D v50 Large-particle chemical substances of cobalt tetroxide, lithium carbonate, magnesium oxide, aluminum oxide, yttrium oxide, strontium oxide, and tungsten oxide (16μm) were weighed according to a lithium / cobalt source ratio of Li / Co = 1.06:1 mol / mol, with each dopant element having a mass percentage of 1000 ppm in the large-particle matrix. The weighed materials were premixed in a self-sealing bag, then added to a Kawada mixer and mixed at 200 rpm for 5 minutes, followed by 1200 rpm for 20 minutes. The homogeneous mixture was then placed in a mortar and placed in a box furnace. The temperature was increased to 1060℃ at a rate of 3℃ / min, and sintered at this temperature for 12 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was performed entirely in an air atmosphere with an air flow rate of 5 m³ / min. 3 / h, after cooling, the material is coarsely crushed using a jaw crusher and a double roller mill, and then finely crushed using an air jet mill to obtain D. v50 It is a large particle matrix of 19.0 μm.
[0221] (2) D v50A 19.0 μm large particle matrix, a low-temperature coating material manganese formate (Mn element mass ratio of 500 ppm of the large particle matrix), a medium-temperature coating material Bi2O3 (Bi mass ratio of 500 ppm of the large particle matrix), and a high-temperature coating material Li2B4O7 (Li2B4O7 mass ratio of 1000 ppm of the large particle matrix) were mixed. The mixed materials were then used in a ball mill mixer with a mass ratio of zirconium balls to the mixture of 1:2. The mixture was mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0222] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 300℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 800℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain large-particle lithium cobalt oxide cathode material, i.e., lithium cobalt oxide cathode material.
[0223] Example 18
[0224] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0225] (1) Refer to Examples 1 and 2.
[0226] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. Low-temperature coating material cobalt nitrate (Co element mass percentage of 500 ppm of the lithium cobalt oxide matrix), medium-temperature coating material Sb₂O₃ (Sb mass percentage of 500 ppm of the lithium cobalt oxide matrix), and high-temperature coating material Li₃PO₄ (Li₃PO₄ mass percentage of 1000 ppm of the lithium cobalt oxide matrix) are mixed. The mixed materials are then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1, and mixed at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0227] (3) The secondary mixture is loaded into a sintering bowl and placed in a box furnace. The temperature is increased to the low-temperature plateau of 100℃ at a heating rate of 2℃ / min, and sintered at this temperature for 5 hours. Then, the temperature is increased to the medium-temperature plateau of 700℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature is increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture is then allowed to cool naturally to room temperature. Sintering is performed entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0228] Example 19
[0229] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0230] (1) Refer to Examples 1 and 2.
[0231] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. Low-temperature coating material cobalt nitrate (Co element mass percentage of 500 ppm of the lithium cobalt oxide matrix), medium-temperature coating material Sb₂O₃ (Sb mass percentage of 500 ppm of the lithium cobalt oxide matrix), and high-temperature coating material Li₃PO₄ (Li₃PO₄ mass percentage of 1000 ppm of the lithium cobalt oxide matrix) are mixed. The mixed materials are then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1, and mixed at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0232] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 200℃ at a heating rate of 2℃ / min, and sintered at this temperature for 3 hours. Then, the temperature was increased to the medium-temperature plateau of 700℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0233] Example 20
[0234] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0235] (1) Refer to Examples 1 and 2.
[0236] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. Low-temperature coating material cobalt nitrate (Co element mass percentage of 500 ppm of the lithium cobalt oxide matrix), medium-temperature coating material Sb₂O₅ (Sb mass percentage of 500 ppm of the lithium cobalt oxide matrix), and high-temperature coating material Li₃PO₄ (Li₃PO₄ mass percentage of 1000 ppm of the lithium cobalt oxide matrix) are mixed. The mixed materials are then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1, and mixed at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0237] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 200℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 400℃ at a heating rate of 2℃ / min, and sintered at this temperature for 3 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0238] Example 21
[0239] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0240] (1) Refer to Examples 1 and 2.
[0241] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. A low-temperature coating material, cobalt nitrate (Co element mass percentage of 500 ppm of the lithium cobalt oxide matrix), a medium-temperature coating material, Sb₂O₅ (Sb mass percentage of 500 ppm of the lithium cobalt oxide matrix), and a high-temperature coating material, Li₃PO₄ (Li₃PO₄ mass percentage of 1000 ppm of the lithium cobalt oxide matrix), are mixed. The mixed materials are then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1, and mixed at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0242] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 200℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 600℃ at a heating rate of 2℃ / min, and sintered at this temperature for 5 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 5 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0243] Example 22
[0244] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0245] (1) Refer to Examples 1 and 2.
[0246] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. A low-temperature coating material, cobalt nitrate (Co element mass percentage of 500 ppm of the lithium cobalt oxide matrix), a medium-temperature coating material, Sb₂O₅ (Sb mass percentage of 500 ppm of the lithium cobalt oxide matrix), and a high-temperature coating material, Li₃PO₄ (Li₃PO₄ mass percentage of 1000 ppm of the lithium cobalt oxide matrix), are mixed. The mixed materials are then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1, and mixed at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0247] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 200℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 600℃ at a heating rate of 2℃ / min, and sintered at this temperature for 5 hours. Finally, the temperature was increased to the high-temperature plateau of 1000℃ at a heating rate of 2℃ / min, and sintered at this temperature for 3 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0248] Example 23
[0249] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0250] (1) Refer to Examples 1 and 2.
[0251] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. Low-temperature coating material cobalt nitrate (Co element mass percentage of 300 ppm in the lithium cobalt oxide matrix), medium-temperature coating material Sb₂O₅ (Sb mass percentage of 1000 ppm in the lithium cobalt oxide matrix), and high-temperature coating material Li₃PO₄ (Li₃PO₄ mass percentage of 1000 ppm in the lithium cobalt oxide matrix) are mixed. The mixed materials are then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1, and mixed at 200 rpm for 3 hours to achieve uniform mixing, resulting in a secondary mixture.
[0252] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 200℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 600℃ at a heating rate of 2℃ / min, and sintered at this temperature for 5 hours. Finally, the temperature was increased to the high-temperature plateau of 950℃ at a heating rate of 2℃ / min, and sintered at this temperature for 3 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0253] Example 24
[0254] This embodiment provides a method for preparing a lithium cobalt oxide cathode material, including the following specific steps:
[0255] (1) Refer to Examples 1 and 2.
[0256] (2) The D prepared in Example 1 v50 The D particles prepared in Example 2 are large particles with a diameter of 19.0 μm. v50 The matrix consists of small particles with a diameter of 5.0 μm and a mass ratio of large particles to small particles of 4:1, forming a lithium cobalt oxide matrix. Low-temperature coating material cobalt nitrate (Co element mass percentage of 1000 ppm of the lithium cobalt oxide matrix), medium-temperature coating material Sb₂O₅ (Sb mass percentage of 300 ppm of the lithium cobalt oxide matrix), and high-temperature coating material Li₃PO₄ (Li₃PO₄ mass percentage of 2000 ppm of the lithium cobalt oxide matrix) are mixed. The mixed materials are then used in a ball mill mixer with a zirconium ball to mixture mass ratio of 1.2:1, and mixed at 200 rpm for 3 hours to obtain a homogeneous secondary mixture.
[0257] (3) The secondary mixture was loaded into a sintering bowl and placed in a box furnace. The temperature was increased to the low-temperature plateau of 200℃ at a heating rate of 2℃ / min, and sintered at this temperature for 4 hours. Then, the temperature was increased to the medium-temperature plateau of 600℃ at a heating rate of 2℃ / min, and sintered at this temperature for 5 hours. Finally, the temperature was increased to the high-temperature plateau of 900℃ at a heating rate of 2℃ / min, and sintered at this temperature for 5 hours. The mixture was then allowed to cool naturally to room temperature. Sintering was carried out entirely in an air atmosphere with an air flow rate of 3 m³ / min. 3 / h, after cooling, the material is mechanically crushed to obtain lithium cobalt oxide cathode material containing large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material.
[0258] Characterization
[0259] Scanning electron microscopy was performed on the lithium cobalt oxide cathode materials of Example 4 and Comparative Example 13. The results are shown in [link to documentation]. Figure 2 and Figure 3 .
[0260] X-ray diffraction was performed on the lithium cobalt oxide cathode material of Example 3, and its XRD pattern is shown in [reference needed]. Figure 4 The results show the presence of LiCoPO4 and SbPO4 phases, indicating the formation of polyanionic substances.
[0261] Experimental Example
[0262] The lithium cobalt oxide cathode materials provided in Examples 1-24 and Comparative Examples 1-13 were mixed with conductive carbon and PVDF at a mass ratio of 95:2:3 in NMP using a homogenizer, and then coated onto aluminum foil. After vacuum drying, the cathode sheets were cut to obtain cathode plates. The cathode plates, lithium metal anode plates, separators, electrolyte (1 mol / L LiPF6 dissolved in an EC / DEC (volume ratio 1:1) mixed solvent with 3 wt% FEC), and a 2032 coin cell casing were assembled into coin cells in a glove box. Capacity testing was then performed with a voltage window of 3.0-4.58V and a discharge rate of 0.1C. Cycling tests were conducted using a full coin cell, with a graphite electrode (active material: conductive carbon: binder = 95:2:3) as the anode, at 45°C, a voltage window of 3.0-4.53V, and a 1C rate for 100 cycles to test cycle performance.
[0263] The results are shown in Table 1.
[0264] Table 1 Test Results
[0265]
[0266]
[0267] According to the test results, as shown in Table 1, the battery cycle retention rates of the embodiments of the present invention using coating materials with different melting points and coated at different temperature gradients were all improved. Comparing Comparative Examples 1, 4, 10, and 11, the capacity was improved to some extent after coating with materials from a low-temperature platform. Comparative Examples 2 and 5 demonstrate that the cycle performance was improved after coating with materials from a medium-temperature platform. Comparative Examples 3 and 6 demonstrate that the first-time efficiency was improved and the impedance was reduced after coating with fast-ion conductor materials from a high-temperature platform, which is beneficial for lithium-ion insertion / extraction. Examples 1, 2, and 3 illustrate that using different temperature gradients during the sintering stage to coat different materials on the surface of the cathode material can further improve capacity and cycle performance.
[0268] Comparative Example 13, Example 4 and Example 5, combined with Figure 2 and Figure 3 This demonstrates that using low, medium, and high temperature platforms can effectively ensure that the coating layer is uniformly coated on the material surface, thereby improving the cycle stability of lithium cobalt oxide cathode materials under high voltage. A single temperature will cause the coated particles to aggregate on the surface, which is not conducive to the uniform formation of the coating layer.
[0269] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A lithium cobalt oxide cathode material, characterized in that, Includes a lithium cobalt oxide matrix and a multifunctional coating layer covering the lithium cobalt oxide matrix; The lithium cobalt oxide matrix is LiCo. 1-x M x O2; wherein the doping element M includes any one or more of the following elements: Zn, Ti, Fe, Mg, Al, Y, La, Zr, Sr, W, Nb, Ta, Ba, Sb, Te, Bi, and Sn; 0.0001≤X≤0.1; The multifunctional coating layer comprises LiQO2, a compound stabilizing lithium cobalt oxide crystals, and a fast ion conductor; wherein, Q in LiQO2 includes any one or more of Ni, Co, and Mn; the LiQO2 is formed from a low-temperature coating material with a melting point of 100-300℃; the compound stabilizing lithium cobalt oxide crystals is formed from a medium-temperature coating material with a melting point of 400-800℃; the fast ion conductor is formed from a high-temperature coating material with a melting point of 850-1000℃; the multifunctional coating layer further includes a polyanionic compound; the medium-temperature coating material includes Sb2O3 and Sb2O3. 5、 Any one or more of TeO2, Bi2O3, B2O3, MoO3, V2O5, SeO2, ZrCl4 and NaAlF4.
2. The lithium cobalt oxide cathode material according to claim 1, characterized in that, The high-temperature coating material includes any one or more of Li3PO4, Li2SO4, LiF, LiBO2, and Li2B4O7.
3. The lithium cobalt oxide cathode material according to claim 1, characterized in that, The low-temperature coating material includes nickel nitrate, cobalt nitrate, manganese nitrate, nickel formate, cobalt formate, manganese formate, and C. 10 H 16 CoO4, C 10 H 14 NiO4 and C 15 H 21 Any one or more of MnO6.
4. The lithium cobalt oxide cathode material according to claim 1, characterized in that, The lithium cobalt oxide cathode material includes large-particle lithium cobalt oxide cathode material and small-particle lithium cobalt oxide cathode material, wherein the particle size of the large-particle lithium cobalt oxide cathode material is 16μm≤D. v50 The particle size of the small-particle lithium cobalt oxide cathode material is ≤20μm, and the particle size is 3μm≤D. v50 ≤6μm.
5. The lithium cobalt oxide cathode material according to claim 4, characterized in that, The mass ratio of the large-particle lithium cobalt oxide cathode material to the small-particle lithium cobalt oxide cathode material is 2:1-4:
1.
6. A method for preparing the lithium cobalt oxide cathode material according to any one of claims 1-5, characterized in that, include: The lithium cobalt oxide matrix, low-temperature coating material, medium-temperature coating material, and high-temperature coating material are mixed and then sintered in multiple stages. Multi-stage sintering includes: low-temperature sintering, medium-temperature sintering, and high-temperature sintering.
7. The preparation method according to claim 6, characterized in that, The lithium cobalt oxide matrix includes a large particle matrix and a small particle matrix; Wherein, the particle size of the large particle matrix is 16μm≤D v50 ≤20μm; The particle size of the small particle matrix is 3μm≤D v50 ≤6μm.
8. The preparation method according to claim 7, characterized in that, The mass ratio of the large particle matrix to the small particle matrix is 2:1 to 4:
1.
9. The preparation method according to claim 6, characterized in that, The preparation steps of the lithium cobalt oxide matrix include: mixing a cobalt source, a lithium source and a dopant and then sintering at high temperature.
10. The preparation method according to claim 7, characterized in that, The high-temperature sintering conditions for forming the large particle matrix include: a temperature of 1020-1060℃ and a time of 8-12 hours; The high-temperature sintering conditions for forming the small particle matrix include: a temperature of 980-1030℃ and a time of 8-12 hours.
11. The preparation method according to claim 9, characterized in that, The cobalt source includes large-particle cobalt sources and small-particle cobalt sources; The large-particle cobalt source has a particle size of 14 μm ≤ D. v50 ≤18μm; the particle size of the small cobalt source is 2μm≤D v50 ≤7μm.
12. The preparation method according to claim 9, characterized in that, The molar ratio of Co in the cobalt source to Li in the lithium source is Li / Co = 1.02~1.09:
1.
13. The preparation method according to claim 9, characterized in that, The amount of dopant is calculated based on the content of the corresponding dopant element in the lithium cobalt oxide matrix, and the mass percentage of the dopant element in the lithium cobalt oxide matrix is 300-1000 ppm.
14. The preparation method according to claim 9, characterized in that, The doping element in the dopant includes any one or more of Zn, Ti, Fe, Mg, Al, Y, La, Zr, Sr, W, Nb, Ta, Ba, Sb, Te, Bi, and Sn.
15. The preparation method according to claim 9, characterized in that, The cobalt source includes any one or more of cobalt carbonate, cobalt tetroxide, cobalt hydroxyoxide, cobalt hydroxide, and cobalt oxalate; The lithium source includes any one or more of lithium carbonate, lithium hydroxide, and lithium oxide.
16. The preparation method according to any one of claims 6-15, characterized in that, The conditions for low-temperature sintering in multi-stage sintering include: a temperature of 100-300℃ and a holding time of 3-5 hours; and / or, The conditions for medium-temperature sintering include: 400-800℃, with a holding time of 3-5 hours; and / or, The conditions for high-temperature sintering include: 850-1000℃, and a holding time of 3-5 hours.
17. The preparation method according to any one of claims 6-15, characterized in that, The low-temperature coating material contains any one or more of the following elements: Ni, Co, and Mn; and the mass of each element accounts for 300-1000 ppm of the lithium cobalt oxide matrix. The intermediate-temperature coating material contains any one or more of the following elements: Sb, Te, Bi, B, Mo, V, Se, Zr, Al, and Na; and the mass of each element accounts for 300-1000 ppm of the lithium cobalt oxide matrix. Each of the high-temperature coating materials accounts for 1000-2000 ppm of the lithium cobalt oxide matrix.
18. A positive electrode plate, characterized in that, It includes the lithium cobalt oxide cathode material as described in any one of claims 1-5.
Citation Information
Patent Citations
Surface-modified lithium cobaltate material and preparation method thereof
CN103606674A
Positive electrode material and preparation method thereof, positive plate, lithium ion battery and electric equipment
CN117543018A
